The positive effects of appropriate drought stress on alfalfa that saving water while ensuring quality and economic benefits - Liying Liu; Haoran Yu; Yuzhi Wang; Yahong Liu; Hongmei Liu; Yiwen Yang; Ruiting Jia; Yinghao Liu (Plant Production Science)
Irrigation and harvest management play a fundamental role in sustaining alfalfa (Medicago sativa) productivity in regions of northern China with a sandy-soil. Temporary drought stress at single growth stage can help to balance yield outcome and water input. However, few studies have found a suitable practice of combination of drought stress and harvesting strategies to increase the alfalfa production and reduce water consumption. Here, we compared the effect of various harvesting regimes (five harvesting stage and four mowing heights) and three irrigation levels (drought stress) on forage yield and quality of alfalfa. The results showed that the effects of the three conditional parameters were interconnected. Moderate drought stress hardly affected yields compared to standard irrigation practices, but it improved water use efficiency. In contrast, severe drought stress reduced yields and CP content, while it increased the fiber content of the hay. Maximum hay yields and nutritional quality were obtained by applying single irrigation doses at moderate drought level, applied 7 days before the plants reached branching and again 7 days before harvesting at budding. This irrigation and harvesting modus can potentially increase the local alfalfa production, while water consumption is reduced by 22%, it would also result in a benefit of 3.46 CNY per m3 of water. Changing local practices to these recommendations would contribute to a more effective use of the scarce water supply for alfalfa production in sandy soils of north China. This is important in view of the projected effects of future climate changes.